Optimization of Water Resources to Counteract the Effects of Water Deficit Using the WEAP Model - Laveriano, Elian Bayona (2024)
The water deficit generates a great impact in regions where demand for this resource is of vital importance for socioeconomic development. The high concentration of urban centres, the poor management of the resource, the various climatic changes, are some of the factors that cause its limitation. This research aims to analyze the best alternative to optimize the resource and meet the demands in areas where its availability and supply are scarce. A hydrological simulation model of the Coata River Basin (CRB) was carried out using the Water Assessment and Planning System (WEAP). Data such as precipitation, temperature, relative humidity, wind speed, and flow were extracted from the historical records of 10 rainfall stations for a period of 50 years (1971-2022). Three scenarios were established in the CRB, the construction of a dam (S1), the implementation of a diversion (S2) and the implementation of a sprinkler irrigation system (S3). The results revealed that S1 has a supply of 1103.1 MMC and a demand of 1308.4 MMC, leaving an unsatisfied demand of 205.3 MMC. The S2 has a supply of 1103.1 MMC and a demand of 1285.6 MMC, leaving an unsatisfied demand of 182.5 MMC. Finally, the S3 presents a supply of 1103.1 MMC and a demand of 912.3 MMC, with the demand for water being fully covered. The implementation of a sprinkler irrigation system proved effective in improving the volume of water required in the CRB.